Survey of seasonality in the Caribbean macroeconomic variables - Maurin, Alain ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Offers a review of the literature on tests for unit roots in presence of seasonality, through numerous applications on Caribbean data.